Antimicrobial Resistance of Enterobacteriaceae Isolates from Chicken Eggs Sold at Bukidnon, Philippine - Sajol, Philip John; Tanutan, Rose Pearl S.; Torres, Jhay Bonn Mark C.; Jimenez, Vingelle Bautista; Montemayor, Maria Lebeña; Obedencio, Jose Jr. (Universitas Airlangga, 2025)
The isolation of Enterobacteriaceae from chicken eggs and their antimicrobial resistance was investigated. The study utilized various selective, differential, and biochemical media for the isolation and identification of the organisms. The Kirby-Bauer disk diffusion method was then used to assess resistance to four commonly used antimicrobials. Results were interpreted based on reference values set by the Clinical Laboratory Standards Institute. A total of 101 Enterobacteriaceae organisms, including Citrobacter spp., Escherichia coli, Enterobacter spp., Klebsiella spp., Proteus spp., Salmonella spp., Serratia spp., and Shigella spp., were identified from eggshell surfaces and egg contents. In decreasing order of the number of resistant isolates, the bacterial isolates showed resistance to ampicillin, followed by trimethoprim-sulfamethoxazole, ciprofloxacin, and doxycycline. Multidrug resistance patterns were observed, with numerous representative bacterial isolates showing resistance to all antimicrobials. The findings highlight a public health concern and underscore the need for enhanced monitoring of antimicrobial-resistant bacteria in food sources, the judicious use of antimicrobials in poultry layer production, improved hygiene practices in food production and handling, and recommendations for further research to better understand resistance mechanisms.